2021
DOI: 10.1007/s00392-021-01856-5
|View full text |Cite
|
Sign up to set email alerts
|

Prospective blinded evaluation of smartphone-based ECG for differentiation of supraventricular tachycardia from inappropriate sinus tachycardia

Abstract: Introduction Supraventricular tachycardias (SVT) are often difficult to document due to their intermittent, short-lasting nature. Smartphone-based one-lead ECG monitors (sECG) were initially developed for the diagnosis of atrial fibrillation. No data have been published regarding their potential role in differentiating inappropiate sinus tachycardia (IST) from regular SVT. If cardiologists could distinguish IST from SVT in sECG, economic health care burden might be significantly reduced. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…In comparison, in the present study of single-lead ECGs cardiologists agreed on the diagnosis of 86.1% of ECGs (1,587 out of 1,843 ECGs). However, the proportion of normal ECGs included in this study was substantially lower than in the SAFE AF Screening Trial (less than 1% in this study, versus 𝜅 = 0.76 when using single-lead ECGs from the same patients(17).The previously reported levels of agreement for the diagnosis of AF from single-lead ECGs have varied greatly between studies: fair agreement was observed by Kearley et al(18) (𝜅 = 0.28); moderate agreement was observed byLowres et al…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…In comparison, in the present study of single-lead ECGs cardiologists agreed on the diagnosis of 86.1% of ECGs (1,587 out of 1,843 ECGs). However, the proportion of normal ECGs included in this study was substantially lower than in the SAFE AF Screening Trial (less than 1% in this study, versus 𝜅 = 0.76 when using single-lead ECGs from the same patients(17).The previously reported levels of agreement for the diagnosis of AF from single-lead ECGs have varied greatly between studies: fair agreement was observed by Kearley et al(18) (𝜅 = 0.28); moderate agreement was observed byLowres et al…”
mentioning
confidence: 60%
“…However, the proportion of normal ECGs included in this study was substantially lower than in the SAFE AF Screening Trial (less than 1% in this study, versus 93% in SAFE), so the simple level of agreement is not directly comparable. Similarly, in a study of the diagnosis of supraventricular tachycardia in hospital patients, an almost perfect agreement of 𝜅 = 0.97 was observed in interpretation of 12-lead ECGs, compared to a substantial agreement of 𝜅 = 0.76 when using single-lead ECGs from the same patients (17). The previously reported levels of agreement for the diagnosis of AF from single-lead ECGs have varied greatly between studies: fair agreement was observed by Kearley et al (18) (𝜅 = 0.28); moderate agreement was observed by Lowres et al (19) (weighted 𝜅 = 0.4); substantial agreements were observed by Poulsen et al (12) (𝜅 = 0.65) and Kearley et al (18) (𝜅 = 0.76); and almost perfect agreements were observed by Desteghe et al (11)(𝜅 = 0.69 to 0.86), Koshy et al (20) (𝜅 = 0.80 to 0.83), Wegner et al (13) (𝜅 = 0.90), and Racine et al (21)(𝜅 = 0.94).…”
Section: Discussionmentioning
confidence: 86%
“…On the other hand, the presence of ventricular pacing or atrial flutter often leads to misclassification of AF as sinus rhythm. 32 These issues will limit accuracy of AF algorithms in consumer-facing devices.…”
Section: Algorithms/ai Used For Af Diagnosismentioning
confidence: 99%
“…En la actualidad el mundo ha evolucionado y la tecnología ha evolucionado por lo que realizó con un grupo de estudio de 75 pacientes de un área específica de salud con un teléfono moderno inteligentes que fue de utilidad diagnóstica que beneficiara a los médicos a dar un diagnóstico certero y seguro y confiable (3).…”
Section: Introductionunclassified